Unhappy Young People. Has Postmodernity Failed Young People? - Rutkowski, Jan (Paedagogia Christiana, 2026)
The article attempts to answer the question of why young people’s well-being is deteriorating. Why, despite the incredible progress being made in the sciences of education, are the young increasingly unhappy? Why are mental illnesses and suicide attempts on the rise? A thesis has been proposed that young people feel disillusioned by the unfulfilled promises of postmodernity. Modernity and postmodernity promised solutions to age-old human problems consisting of poverty, illness, death, the need to work and sexual problems. Christianity promised its faithful followers a solution to these problems only after death. Modern and post-modern ideologies argue that it is possible to create a ‘paradise’ on earth. However, they do not fulfill these promises. The so-called incels were cited as an example of a disillusioned group.